The Use of Grammarly in the Academic Writing of Undergraduate Students: Advantages, Weaknesses, and Challenges (Systematic Review) - Dwi Astuti; Darmahusni Darmahusni; Sri Sumarni; Muchlas Suseno (English Language and Literature International Conference (ELLiC) Proceedings, 2023)
The fact that "Grammarly" is one of the available online grammar checkers has had a quick influence on technological development. The purpose of this study was to examine the benefits, drawbacks, and difficulties of utilizing Grammarly in an academic writing course. This study used qualitative library research. The data was collected from 10 relevant articles on Google Scholar with the keyword "Grammarly, Academic Writing, and undergraduate students". The main issues addressed in this study were the benefits, weaknesses, and challenges of Grammarly in the period from 2019 to 2023 The result showed that there were six categories of advantages in using Grammarly, they were to check correctness, clarity, engagement, delivery, plagiarism, and convenience. On the contrary, the weaknesses of Grammarly were it could not be accessed without an internet connection; it needed stability of electricity and an internet connection, it needed high-speed internet connectivity to access the complete feature; it was ineffective to use Grammarly in another connected platform; it was incomplete service of free version, while it needed to pay to access the premium one; and it could not identify some proer noun.  In conclusion, applying Grammarly is recommended because it enhanced students’ writing skills for students at university, especially in Academic Writing Course.